The investigation of BN nanosheets production by using solvent exfoliation - Dikbas, Halil (Natl Inst Optoelectronics, 2017)
In this study, Boron Nitride Nanosheets (BNNSs) were produced via solvent exfoliation method with hexagonal boron nitride (h-BN) which was used as the raw material. This method is essentially based on separating the layers, which are bound with weak bonds, through a solvent. For this purpose, h-BN powders were firstly exposed to an acidic process and then heat treatment. A new structure with expanded hexagonal layers (expanded hexagonal boron nitride) was obtained at the end of this process. Synthesized expanded hexagonal boron nitride was sonicated in a solvent (N,N dimethylformamide). At the end of the process, synthesized samples were characterized by Scanning electron microscope (SEM), Transmission electron microscope (TEM), UV-Vis absorption spectra, Fourier transform infrared (FTIR) and atomic force microscope (AFM). Consequently, it was found that BNNS layers that had a thickness of several nanometers and a width of a few hundreds of nanometers were produced.
Keywords: Boron nitride; Nanosheet; Solvent exfolation; Synthesis